Cross-Sectional Study on Knowledge and Attitudes of Nonhealth Students Towards The Use of Antibiotics in Bangkalan Regency - April Nuraini; Nafisah Isnawati; Ratri Rokhani (LPPM Universitas Harapan Bangsa, 2024)
Antibiotics are drugs to kill bacteria or slow their growth. Antibiotics should be used at the doctor's clinical discretion and administered to the patient on prescription. The purpose of this study was to determine the relationship of unhealthy student knowledge level to the attitude and behavior of antibiotic use. Descriptive analysis research method with cross sectional approach on unhealthy students in Bangkalan Regency. Sampling was done by purposive sampling technique with questionnaire. The number of samples was 96 respondents conducted in March-May 2024. Analysis of bivariate and mulitivariate data. Data analysis with logistic regression. The results of the study stated that most of the non-health students in Bangkalan have enough knowledge in the category (40.2%), have enough attitude in the category (43.3%) and enough behavior (48.4%). The relationship of students ' level of knowledge to the attitude and behavior of antibiotic use using spearman correlation test that is sig value of 0.000 (<0.05) shows the relationship between the level of knowledge with the attitude and behavior of antibiotic use